DIDACTIC BASIS OF TEACHING PHYSICAL EXERCISES - Kholova Shakhnoza Mardonovna; Musaeva Ma'mura (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: This article discusses the didactic principles of teaching physical exercises, the role of pedagogical methods in their effective implementation, the need to take into account age-specific characteristics and plan the content of classes. It also bases the step-by-step teaching approach to the formation of movement skills in students.